2004
DOI: 10.1124/jpet.103.063586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Galantamine, a Nicotinic Allosteric Potentiating Ligand, on Nicotine-Induced Catecholamine Release in Hippocampus and Nucleus Accumbens of Rats

Abstract: Galantamine, a drug for treatment of Alzheimer's disease, is a novel cholinergic agent with a dual mode of action that inhibits acetylcholinesterase and allosterically modulates nicotinic cholinergic receptors (nAChRs). Nicotine stimulates catecholamine secretion, inducing hippocampal norepinephrine (NE) release, and improves memory consolidation. Thus, the effect of galantamine on nicotine-induced hippocampal NE secretion was investigated. This was compared with the effect of galantamine on nicotine-induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…An in vivo microdialysis study showed that galantamine with nicotine at ineffective doses increased noradrenaline release, although galantamine (3 mg/kg) alone did not affect the release in the hippocampus of rats (33). This study also demonstrated that galantamine enhanced nicotine-stimulated noradrenaline release.…”
Section: Noradrenalinesupporting
confidence: 61%
“…An in vivo microdialysis study showed that galantamine with nicotine at ineffective doses increased noradrenaline release, although galantamine (3 mg/kg) alone did not affect the release in the hippocampus of rats (33). This study also demonstrated that galantamine enhanced nicotine-stimulated noradrenaline release.…”
Section: Noradrenalinesupporting
confidence: 61%
“…Thus, it appears that galantamine enhances dopaminergic activity most effectively at a dose that results only in minor AChE inhibition (Geerts et al, 2005), and the effect may therefore rather be due to allosteric potentiation of nAChRs. In support of this conclusion, a recent study reported that a higher dose of galantamine (3.0 mg/kg s.c.) did not increase dopamine efflux in the nucleus accumbens (Sharp et al, 2004).…”
Section: Discussionmentioning
confidence: 66%
“…Nicotine in vivo stimulated increases in hippocampal and accumbal NE and DA levels. Galantamine stimulated the NE but not the DA response, indicating that different circuits are involved in NE versus DA release, and that there are differences in the responses of cognitive versus reward areas (28). In cortical and hippocampal slices, nicotine-induced NE release was inhibited by cholinergic and glutamatergic antagonists, indicating the participation of acetylcholine receptors on glutamatergic neurons (29).…”
Section: Nicotine-induced Neurotransmitter Changes In Areas Involved mentioning
confidence: 98%